Upaya meningkatkan hasil belajar siswa pada materi penggunaan faktor prima untuk menentukan KPK dan FPB melalui tutor sebaya dan media pembelajaran kartu bilangan kelas VI sekolah dasar - Sukarni, Sukarni (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study is to improve student learning outcomes in the material ofusing prime factors to determine the KPK and FPB through peer tutors and learning media forclass VI number cards at SD Negeri Beji 02 for the 2018/2019 academic year. This type ofresearch is classroom action research. The subjects in this study were grade VI students of SDNegeri Beji 02, Ungaran Timur District, Semarang Regency, for the 2018/2019 academic year,totaling 33 children consisting of 20 boys and 13 girls. This research uses test data collectiontechniques. Data were analyzed quantitatively using proportions, by determining thepercentage of data achievement between before and after the action was given. Learningmathematics using the right method can improve student learning outcomes on the KPK andFPB material. This is evidenced by the increase in student scores from the pre-cycle, Cycle I,and Cycle II. After improving the learning cycle II, the students who completed reached 32students and the class average increased to 83.94.